G281 Making a case for 'consultant delivered care' in paediatrics. (27th April 2015) - Rich, J; Balu, R; Cronin, S
Abstract : Aims: The RCPCH standards, Facing the Future standards highlighted need for changing the paediatric services. An important area of concern is that only 25% of units across the UK in 2013 had a consultant present at times of peak activity. There is evidence that a consultant led service is more efficient, ensures rapid decision making and improves outcomes. We recognised the need to change, but had to reconsider the options for delivering care in more innovative and efficient ways. Methods: We used hospital informatics data to make a clear case for consultant presence for extended hours and studied its impact on outcomes. Data was obtained for all 10015 admissions over 24 months on time of admission, time of discharge and length of stay. Average admissions were 418 per month over 24 months. We used this information (Figures 1 and 2) to define peak activity hours (1200 to 2300 h), demonstrate the need for consultant presence and to implement service changes creating a 'short stay unit'. This data enabled us to make 2 significant changes to the way we ran our services: Changes to job plans for all consultants: To remain available for extended hours working until 2200 and provide rapid clinical decision within an hour. Changes to the Paediatric ward: Rreducing in-patient beds and utilising resources to create a 'Short Stay Unit' functioning between 0800 to 2200 h. Results: Most patients referred to the unit from A&E or GPs received an early senior opinion and commenced treatment within an hour (Figure 3). We reduced the number of admissions by 34.6% over the next 5 months (Figure 4) compared to same months the previous years. Conclusions: Paediatric Consultants in our unit recognised the need for modifications to service and agreed to changes in job plans enabling senior presence and advice till late evenings. We increased resources for assessment of unscheduled attendances to the hospital and provided Consultant delivered care in the extended evening hours. This improved our outcomes for quicker senior review and reduced hospital admissions. There was a percieved ncrease in patient satisfacted due to the reduced waiting time and time for starting treatment. These outcomes clearly make a case for the RCPCH vision of Consultant Delivered Care.